The Relationship Between Toothbrushing Habits and the Prevalence of Caries and Calculus in School-Age Children Grades 1-6 at Galilea Hosana School Elementary School, Medan Selayang District of North Sumatra, Indonesia - Molek; Mangatas Hutagalung; Aldi H. Theo Braga Bangun (Community Medicine and Education Journal, 2024)
School-aged children constitute a demographic that encounters dental and oral health issues. Poor oral and dental hygiene is associated with the development of caries and calculus. The objective of the study was to establish the relationship between teeth brushing practices and the occurrence of dental caries and calculus in elementary school children from grades 1-6 at Galilea Hosana School, located in the Medan Selayang District of North Sumatra. The research conducted at Galilea Hosana School Elementary School, Medan Selayang District, is a descriptive-analytic study with a cross-sectional design. The research sample consisted of 64 elementary school pupils enrolled at Galilea Hosana School, located in the Medan Selayang District. The students were from grades 1 to 6. The data were gathered through the administration of questionnaires and the physical inspection of the mouth cavity and teeth. The Kruskal-Wallis statistical test was employed to examine the data. The research findings indicated that the mean calculus score for students was 1.40 ± 0.74, which falls within the category of moderate calculus. On the other hand, the average scores for caries DEFT and DMFT among students were 2.02 ± 2.36 and 1.42 ± 2.06, respectively, placing them in the low caries category. Out of the total number of students, 29 (45.3%) had sufficient tooth-brushing habits, while 19 kids (29.7%) had commendable tooth-brushing practices. Only 16 students (25%) had inadequate tooth-brushing habits. The Kruskal-Wallis test revealed a statistically significant association (p≤0.05) between teeth brushing behaviors and the occurrence of caries and calculus in school-age children in grades 1-6 at Galilea Hosana School Elementary School, located in the Medan Selayang District of North Sumatra. The research findings indicate a direct relationship between poor tooth-brushing habits and increased levels of calculus and caries.